The Influence of the Visual Auditory Kinesthetic Model (VAK) as an Alternative to Improve Basic Basketball Passing Techniques - Muhammad Noer Fadlan; Wariyati; Dina Hidayati (UNIB Press, 2023)
This study aims to determine the extent to which the Visual Auditory Kinesthetic (VAK) model influences the basic techniques of basketball passing. that the teacher has directed in carrying out the practice directly or in theory that has been taught. Then in this study the authors used a descriptive quantitative research method with a one-group pretest-posttest design model, where the researcher described the results in this study by revealing data in the form of numbers that had been analyzed using the SPSS application. Then the results of this study can be seen in some of the following data from the resulting research, it is known that the resulting significance value of 0.144 is greater than 0.06. So it can be concluded that the data tested is normally distributed. Then test the hypothesis through the paired sample t-test that the resulting average pre-test is 54.62 and 81.30 post-test. Therefore, the results of the post-test were better than the pre-test and the resulting standard deviation was for the pretest 13,240 and for the post-test 9,096. Then the results of the other paired sample t-test showed that the results were sig. (2-tailed) obtained by 0.000 (sig.2-tailed), namely 0.000 <0.06, meaning that there is an influence of the visual auditory kinesthetic model in the results of Improve the basic technique of passing basketball.